Características demográficas e audiológicas da população pediátrica de um centro de referência em saúde auditiva de São Paulo - Avelino, Vera Lúcia Ferreira (2017)
Introduction: Introduction: Early diagnosis of childhood hearing impairment is necessary for the confirmation of auditory status and the beginning of (re) habilitation. These processes are important factors for a better development of the language. The National Policy on Auditory Health Care (PNASA), 2004, establishes and organizes actions to promote hearing health, prevention and identification of hearing problems at all levels of complexity. To this end, the Living Without Boundary Plan, 2011, guarantees the accessibility of people with any type of disability, to all types of services, health, education, transportation and social inclusion. Objective: To characterize demographic and audiological data of the users of a reference center in hearing health, in the city of São Paulo. Method: This is a descriptive, retrospective observational study. Local: The study was developed at the Child Hearing Center (CeAC), Research Laboratory of the Child Hearing Research Line. Patients: A total of 857 patient records were analyzed from August 2010 to June 2015. These patients performed all the exams at the Auditory in the Child Center (CEAC), concluding the audiological diagnosis to define their auditory status. Data collection: The following data were extracted from the medical record of each user: gender, date of birth, area of residence, maternity of birth, whether or not the maternity belonged to the Mãe Paulistana / Stork Network Protection Network, if TANU was performed, If there were indicators of risk for hearing loss in the history of the child, origin of the referral for audiological evaluation, age at the first referral center, age at diagnosis completion and outcome of the audiological diagnosis. Analysis: A descriptive analysis was carried out, with the main focus being the age of the diagnosis, to observe the goal of early diagnosis, determinant in the result of the therapeutic intervention. Afterwards, inferential analyzes were performed to identify which aspects favor or hinder early diagnosis. Results: The results show that 60% of the users were male; The majority were resident in the South region (64.2%); The mean age at the beginning of the diagnosis was 2 months of life; The most prevalent complaint was hearing (54.8%) followed by screening (29.6%); 57.8% of the children performed TANU; The majority of children, on average, complete the diagnosis in the age group over one year old (50.2%), followed by children from 0 to 3 months (18.4%); The most prevalent bilateral hearing loss was profound sensorimotor hearing loss at 12.49%, followed by mild conductive hearing loss (8.52%). Conclusion: According to the results presented in the study, we can consider that, the TANU is being very important for the early diagnosis. However, the demand coming from this type of referral is still low, since its obligation was established at five years. Therefore, it is important to raise the awareness of those responsible for children, as well as the professionals who work in this area, in order to achieve greater adherence to the test, and subsequently reach a higher number in this type of demand